Wilfully submitting to and publishing in predatory journals - a covert form of research misconduct? - Yeo-Teh, Nicole Shu Ling (Array, 2021)
A predatory journal could be provisionally defined as one masquerading as a genuine academic publication but offer little, if any, rigorous peer review. Predatory journals or publishers place a focus on maximising financial profit, as opposed to regulated dissemination of scientific advancements. As a result, authors can often get their work published in such journals with little scrutiny on quality. Although generally warned against and discouraged, universally practiced sanctions against researchers" submission to and publication in predatory journals are not common. Predatory publishing thus remains prevalent, particularly in places where academic success is measured by the quantity rather than quality of publication output, which feeds the journal"s business model that thrives upon significant market demand. However, such an undesirable enterprise has the potential to flood the scientific literature with unsound research that could be misleadingly perceived as authoritative. This may result in or add to the confusion of policy makers and the layperson, consequentially bringing disrepute to science and all parties involved. Here, we argue that wilfully submitting one"s manuscript to a predatory journal may constitute an active act of avoidance of rigorous peer review of one"s work. If such is the intention, it would be a questionable research practice and could be considered an, albeit covert, form of scientific misconduct. If labelled as such, and with institutional and funding rules erected to discourage the practice, predatory publishing could be effectively put out of business through diminishing the consumer demand.